2021
DOI: 10.1016/j.jcmgh.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Dysbiosis Amplifies Acetaminophen-Induced Acute Liver Injury

Abstract: Proton pump inhibitor or long-term antibiotics intake, which have been linked to intestinal dysbiosis, are associated with increased risk of acute liver failure in the 500,000 participants of the UK BioBank population-based cohort. In mice, APAP intoxication prompts intestinal dysbiosis, barrier impairment, and bacterial translocation. Dysbiotic microbiota of Nlrp6-/mice induces a Ly6C hi phenotype of hepatic monocyte-derived macrophages and amplifies acute liver injury, a phenotype that is transferable to WT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 75 publications
2
56
0
Order By: Relevance
“…Similarly, compared with wild-type mice, Nlrp6 − /− mice (an intestinal dysbiosis model) also showed that microbial dysbiosis could aggravate APAP-induced liver injury. This phenotype was reproduced after fecal bacteria transplantation (Elinav et al, 2018 ; Schneider et al, 2020 ).…”
Section: The Gut Microbiota and Apap-induced Liver Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, compared with wild-type mice, Nlrp6 − /− mice (an intestinal dysbiosis model) also showed that microbial dysbiosis could aggravate APAP-induced liver injury. This phenotype was reproduced after fecal bacteria transplantation (Elinav et al, 2018 ; Schneider et al, 2020 ).…”
Section: The Gut Microbiota and Apap-induced Liver Injurymentioning
confidence: 99%
“…Schneider KM et al analyzed a cohort of 500,000 participants in the British Biobank and found that proton pump inhibitors (PPI) or long-term antibiotics (ABX) can cause intestinal microbial dysbiosis. The risk of ALF induced by APAP was significantly increased in participants with intestinal microbial dysbiosis (Schneider et al, 2020 ). Similarly, compared with wild-type mice, Nlrp6 − /− mice (an intestinal dysbiosis model) also showed that microbial dysbiosis could aggravate APAP-induced liver injury.…”
Section: The Gut Microbiota and Apap-induced Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…In patients, alcoholic liver disease was associated with low levels of intestinal microbiota-derived tryptophan metabolites, underscoring the clinical impact of the AHR pathway in alcoholic liver disease [49]. Interestingly, the alteration in gut microbiota composition has also been implicated as a risk factor for exacerbated acetaminophen-induced acute liver injury [51]. Although here, the underlying molecular mechanisms were not focus of the study, it is likely that dysbiosis was accompanied with changes in gut bacteria-derived metabolites, including AHR ligands.…”
Section: Ahr and The Gut-liver Axismentioning
confidence: 99%
“…However, even relatively advanced PBPK models consider individual organs as single compartments (Thiel et al 2015 ) or at most differentiate a limited number of compartments within one organ (Bartl et al 2015 ; Ghallab et al 2016 ; Schliess et al 2014 ). Relatively little is known about local concentrations in sub-compartments of tissues (Reif et al 2017 ; Schneider et al 2021 ; Schuran et al 2021 ). Experimentally, local distributions of test compounds in tissues can be analyzed by autoradiography (Groothuis et al 1982 ).…”
Section: Introductionmentioning
confidence: 99%